The law, the market, the gendered subject: workplace sexual harassment in Chennai's information technology industry - Shakthi, S. (Gender, place and culture : a journal of feminist geography, 2020)
The Indian information technology (IT) industry has, in recent years, been plagued by reports of workplace sexual harassment, disrupting the narrative of empowerment disseminated by an industry that projects itself as a pioneer in the area of gender equality. This has been further complicated by the passage of domestic legislation in 2013 mandating companies to form internal committees that will address complaints of workplace sexual harassment. This article, which has emerged out of nine months of ethnographic research on the IT industry in the South Indian city of Chennai, uses a socio-legal approach to unpack the processes and practices through which the law has been interpreted and executed, while also interrogating the law itself as a mechanism for social justice. As I argue in this article, policies for promoting diversity and inclusion in the urban Indian workplace, placed in the context of corporate adherence to the law, can themselves function as significant sites of tension in middle-class women's undertaking of paid employment.